Under the Surface : Fracking, Fortunes, and the Fate of the Marcellus Shale - Wilber, Tom; Wilber, Tom (Book collections on Project MUSE., 2015)
Wilber's evenhanded treatment gives a voice to all constituencies, including farmers and landowners tempted by the prospects of wealth but wary of the consequences, policymakers struggling with divisive issues, and activists coordinating campaigns based on their respective visions of economic salvation and environmental ruin. Wilber describes a landscape in which the battle over the Marcellus ranges from the very local--yard signs proclaiming landowners' allegiances for or against shale gas development--to often conflicting municipal, state, and federal legislation intended to accelerate, delay, or discourage exploration.For millions of people with a direct stake in shale gas exploration in the Marcellus or any number of other emerging shale resources in the United States and worldwide, or for those concerned about the global energy outlook, Under the Surface offers a worthwhile and engaging look at the issues.